Sows turned unhindered at less than their own body length - implications for farrowing pen design - Moustsen, Vivi A.; Baxter, Emma M.; Boldsen, Søren Kjærgaard; Nielsen, Mai Britt Friis; Edwards, Sandra A. (Frontiers in Animal Science, 2025)
Periparturient and lactating sows need to turn around when expressing important nest-building and piglet-gathering behaviors. To determine the minimum pen width required to allow unhindered turning, 26 Danish crossbred sows were selected in late gestation to represent younger (parity 2-4) and mature (parity 5-6) ages. A test pen measured 2.6m on one side, with the other side being adjustable in intervals of 0.2m (1.2–2.2m). Each sow was encouraged to make three food-motivated turns at each of the 6 pen widths according to a randomized design. Direct observations of the time taken to complete a turn and a subjective score of turning difficulty (range 1-6) were supplemented by automated analysis of video recordings, measuring the maximum curvature of the body during a turn and the proximity to the pen walls at the time of maximum curvature. Turns took longer to complete when pen width was 1.2m and 1.4m. Inability to complete some turns occurred at 1.2m and more turns were scored as hindered when pen width was ≤1.6m. Older, larger sows were more frequently hindered. Body curvature during a turn was greater when pen width was 1.2m, while distance from pen walls at maximum curvature only increased in pen widths of ≥1.8m. In conclusion, the trial indicated that a minimum width of 1.6m should be provided to allow unhindered turning for the full grown late pregnant sows. This should be factored into a suitable overall farrowing pen design for loose sows to avoid negative impacts on sow and piglet welfare.